Consenso latinoamericano: niños pequeños para la edad gestacional (2012)
Background Children born small for gestational age (SGA) experience higher rates of morbidity and mortality than those born appropriate for gestational age. In Latin America, identification and optimal management of children born SGA is a critical issue. Leading experts in pediatric endocrinology throughout Latin America established working groups in order to discuss key challenges regarding the evaluation and management of children born SGA and ultimately develop a consensus statement. Discussion SGA is defined as a birth weight and/or birth length greater than 2 standard deviations (SD) below the population reference mean for gestational age. SGA refers to body size and implies length-weight reference data in a geographical population whose ethnicity is known and specific to this group. Ideally, each country/region within Latin America should establish its own standards and make relevant updates. SGA children should be evaluated with standardized measures by trained personnel every 3 months during year 1 and every 6 months during year 2. Those without catch-up growth within the first 6 months of life need further evaluation, as do children whose weight is ≤ -2 SD at age 2 years. Growth hormone treatment can begin in SGA children > 2 years with short stature (< -2.0 SD) and a growth velocity < 25th percentile for their age, and should continue until final height (a growth velocity below 2 cm/year or a bone age of > 14 years for girls and > 16 years for boys) is reached. Blood glucose, thyroid function, HbA1c, and insulin-like growth factor-1 (IGF-1) should be monitored once a year. Monitoring insulin changes from baseline and surrogates of insulin sensitivity is essential. Reduced fetal growth followed by excessive postnatal catch-up in height, and particularly in weight, should be closely monitored. In both sexes, gonadal function should be monitored especially during puberty. Summary Children born SGA should be carefully followed by a multidisciplinary group that includes perinatologists, pediatricians, nutritionists, and pediatric endocrinologists since 10% to 15% will continue to have weight and height deficiency through development and may benefit from growth hormone treatment. Standards/guidelines should be developed on a country/region basis throughout Latin America.